Treatment of carcinoma in situ of larynx: surgery versus radiotherapy - Antunes, Joselina (2022)
Objectives: Evaluate the results of different treatments used in the treatment of in situ squamous cell carcinoma of the larynx. Methods: Observational study that included patients followed in Instituto Português de Oncologia of Lisbon. The study included a group of patients with a diagnosis of in situ squamous cell carcinoma of the larynx, diagnosed between 2006 and 2018, and treated with surgery or radiotherapy. Results: The study included 59 patients, 46 of these patients were submitted for surgery and 13 patients for radiotherapy. A median follow-up of 63,0 months (30,0-97,0) was made, and it was observed that recurrent disease in 25,4% of the total population, 26,1% of the patients that were submitted to surgery, and 23,1% of the ones that were submitted to radiotherapy. No statistically significant differences were found in recurrent disease between treatments used. Conclusions: On this study, both treatments allow good local control rates of the disease, without differences between them.